Comparison of Spasticity in Spinal cord Injury and Stroke Patients Using Reflex Period in Pendulum Test - Kristjana Kristinsdottir; Gigja Magnusdottir; Belinda Chenery; Vilborg Gudmundsdottir; Halla Kristin Gudfinnsdottir; Halldor Karason; Gudbjorg Ludvigsdottir; Thordur Helgason (PAGEPress Publications, 2020)
Spasticity is a motor impairment present in patients with both stroke and spinal cord injury. In this research, the results from the Wartenberg pendulum test, performed on stroke and spinal cord injury patients using goniometers and electromyogram recordings of the quadriceps, were reviewed and a new parameter to quantify spasticity was extracted. The Reflex Period (RP) of the pendulum test was defined as the time span from 50% of the maximum velocity of the leg swing to the activation of muscle contraction in the quadriceps, determined from the EMG. The results suggest that the reflex period in stroke patients is generally shorter than in those suffering from spinal cord injury.